Subcellular calcium dynamics in a whole-cell model of an atrial myocyte - Thul, Ruediger; Coombes, Stephen; Roderick, H. Llewelyn; Bootman, Martin D. (National Academy of Sciences, 2012)
In this study, we present an innovative mathematical modeling approach that allows detailed characterization of Ca(2+) movement within the three-dimensional volume of an atrial myocyte. Essential aspects of the model are the geometrically realistic representation of Ca(2+) release sites and physiological Ca(2+) flux parameters, coupled with a computationally inexpensive framework. By translating nonlinear Ca(2+) excitability into threshold dynamics, we avoid the computationally demanding time stepping of the partial differential equations that are often used to model Ca(2+) transport. Our approach successfully reproduces key features of atrial myocyte Ca(2+) signaling observed using confocal imaging. In particular, the model displays the centripetal Ca(2+) waves that occur within atrial myocytes during excitation-contraction coupling, and the effect of positive inotropic stimulation on the spatial profile of the Ca(2+) signals. Beyond this validation of the model, our simulation reveals unexpected observations about the spread of Ca(2+) within an atrial myocyte. In particular, the model describes the movement of Ca(2+) between ryanodine receptor clusters within a specific z disk of an atrial myocyte. Furthermore, we demonstrate that altering the strength of Ca(2+) release, ryanodine receptor refractoriness, the magnitude of initiating stimulus, or the introduction of stochastic Ca(2+) channel activity can cause the nucleation of proarrhythmic traveling Ca(2+) waves. The model provides clinically relevant insights into the initiation and propagation of subcellular Ca(2+) signals that are currently beyond the scope of imaging technology.